Chimeric Antigen Receptor T-Cells: An Overview of Concepts, Applications, Limitations, and Proposed Solutions - Alnefaie, Alaa; Albogami, Sarah; Asiri, Yousif; Ahmad, Tanveer; Alotaibi, Saqer S.; Al-Sanea, Mohammad M.; Althobaiti, Hisham (Frontiers in Bioengineering and Biotechnology, 2022)
Adaptive immunity, orchestrated by B-cells and T-cells, plays a crucial role in protecting the body from pathogenic invaders and can be used as tools to enhance the body’s defense mechanisms against cancer by genetically engineering these immune cells. Several strategies have been identified for cancer treatment and evaluated for their efficacy against other diseases such as autoimmune and infectious diseases. One of the most advanced technologies is chimeric antigen receptor (CAR) T-cell therapy, a pioneering therapy in the oncology field. Successful clinical trials have resulted in the approval of 5 CAR-T cell products by the Food and Drug Administration for the treatment of hematological malignancies. However, there have been various obstacles that limit the use of CAR T-cell therapy as the first line of defense mechanism against cancer. Various innovative CAR-T cell therapeutic designs have been evaluated in preclinical and clinical trial settings and have demonstrated much potential for development. Such trials testing the suitability of CARs against solid tumors and HIV are showing promising results. In addition, new solutions have been proposed to overcome the limitations of this therapy. This review provides an overview of the current knowledge regarding this novel technology, including CAR T-cell structure, different applications, limitations, and proposed solutions.